Theatrical Iconography, Jeu de Scène, and Recognizing the 'Table Scene(s)' in Molière's Tartuffe. (1st July 2013) - Muller, David G
<x xml:space="preserve">Abstract</x> Many recent discussions of the Chauveau and Brissart frontispieces to Molière's Tartuffe have sought to discourage their use as documentary evidence for original performance practice on the grounds that their depiction does not conform to the text of the play. This article re-examines the textual and iconographic evidence for staging the 'table scene', suggesting that these frontispieces may still possess significant documentary value and cannot be so easily rejected as disaffirming the original Jeu de Scène. A close reading of the 1669 text as a script for performance reasserts the continuity between the text and these illustrations despite the hermeneutics of suspicion that pervade recent interpretations that rightly seek to emphasize the illustrations' material function as liminary engravings within books.